ANALISIS HASIL UJI KOMPETENSI GURU TAHUN 2015 DI PROVINSI NUSA TENGGARA TIMUR - Bahruddin, Siti Arafah; In?am, Akhsanul; Lendriyono, Fauzik (Program Studi Magister Pedagogi, 2019)
Abstract: Educators are the spearhead of the success of the continuity of education in the industrial revolution era 4.0. The success of education can be seen in the competencies held by the teacher. This study aims to analyze the result of the Teacher Competency Test (UKG) Year 2015 in East Nusa Tenggara Province. This study used a descriptive quantitative approach and supported by qualitative. This study is descriptive. The subject of this research was the value of teachers who followed UKG Year 2015 in East Nusa Tenggara Province, which consists of 9.286 teachers from 22 districts of East Nusa Tenggara Province. The data were collected by using document and interview techniques. In analyzing the data, the researcher used descriptive statistics and SPSS program to know the Mean value of teachers from the pedagogical and professional competencies. The result of Teacher Competency Test (UKG) Year 2015 in East Nusa Tenggara Province, reviewed from the pedagogical and professional competencies and the general subjects of the national examination (Bahasa Indonesia, English, and Mathematics) of the 22 districts, is relatively categorized low since the Mean value is below the Minimum Competency Standard (SKM) which is 55. According to the functionary and the teachers, several factors cause the low competency of teachers in East Nusa Tenggara Province, so the coordination among the Education Quality Insurer Agency (LPMP), provincial education authorities, and district education authorities should be improved to see the Teacher Competency Test (UKG) problem as a mutual concern. The government should conduct a teacher competency test periodically to maintain the teachers? competencies in both pedagogical and professional to improve the education quality in East Nusa Tenggara Province particularly.Keywords: Teacher, Pedagogical and Professional, Competency Test Abstrak: Pendidik merupakan ujung tombak keberhasilan keberlangsungan pendidikan di era revolusi industri 4.0. Keberhasilan pendidikan dapat dilihat pada kompetensi yang dimiliki oleh guru. Tujuan penelitian ini adalah untuk menganalisis hasil Uji Kompetensi Guru (UKG) Tahun 2015 di Provinsi Nusa Tenggara Timur. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Subyek penelitian ini adalah nilai guru yang mengikuti UKG Tahun 2015 di Provinsi Nusa Tenggara Timur (NTT) sebanyak 9.286 guru di 22 Kabupaten/Kota se Provinsi NTT. Pengumpulan data penelitian dilakukan dengan teknik dokumen dan wawancara. Data penelitian dianalisis dengan deskriptif statistik dan menggunakan program SPSS untuk mengetahui nilai rata-rata guru dari kompetensi pedagogi dan profesional. Hasil UKG Tahun 2015 di Provinsi Nusa Tenggara Timur ditinjau dari kompetensi pedagogi dan profesional berdasarkan 22 Kabupaten/Kota maupun berdasarkan mata pelajaran umum ujian nasional (Bahasa Indonesia, Bahasa Inggris, dan Matematika) secara keseluruhan mencapai nilai rata-ratanya dalam kategori rendah karena dibawah Standar Kompetensi Minimum (SKM) yaitu 55. Menurut pejabat dan guru ada faktor yang menyebabkan rendahnya kompetensi guru di Provinsi NTT, sehingga harus meningkatkan kerja sama antara Lembaga Penjamin Mutu Pendidikan (LPMP), dinas pendidikan Provinsi dan dinas pendidikan Kabupaten/Kota untuk memperhatikan masalah UKG sebagai perhatian bersama. Pemerintah perlu mengadakan sebuah uji kompetensi guru secara berkala, Uji Kompetensi tersebut dimaksudkan agar tetap menjaga kompetensi guru baik pedagogi maupun profesional sehingga dapat meningkatkan kualitas pendidikan di Provinsi NTT pada khususnya.Kata kunci: Guru, Pedagogi dan Profesional, Uji Kompetensi